Prognostic Value of Hyperuricemia on Clinical Outcomes of Sepsis: - T, Sivaranjani; Rebayudeen S M, Mohamed; Geetha, Jeganathan; B, Prabakar (Journal of Neonatal Surgery, 2025)
Background: Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection. Recent studies suggest that metabolic disturbances, including hyperuricemia, may influence the clinical course of sepsis. Uric acid, an end product of purine metabolism, has pro-inflammatory properties that may exacerbate organ dysfunction in septic patients and hence used as a marker of poor prognosis in sepsis. Hyperuricemia and its potential association with poor clinical outcomes, such as acute kidney injury (AKI), need for vasopressor support, mechanical ventilation, and mortality, remains an area of growing interest. This study investigates the association between hyperuricemia and clinical outcomes in adult sepsis patients admitted to the Medical Intensive Care Unit (MICU). Methods: This retrospective analytical study included 162 adult patients diagnosed with sepsis and admitted to the MICU of Karpaga Vinayaga Medical College Hospital, Chengalpattu, Tamil Nadu, India, between January 2024 and December 2024. Adult patients who met Sepsis-3 definition of sepsis is included in this study. Serum uric acid levels, Lactate levels, Creatinine value at the time of admission and after 24 hours of admission were noted. Serum Uric acid levels more than 7 mg/dL is considered as hyperuricemia. Patients were divided into hyperuricemia (n=107) and normouricemia (n=55) groups based on serum uric acid levels. Baseline characteristics, laboratory parameters, AKI, duration of hospital stay, need for vasopressor support, need for assisted mechanical ventilation and mortality outcomes were compared between the groups using appropriate statistical tests, including Fisher’s exact test and chi-square analysis. Results: The median age was 59.5 years, with a female predominance (60.49%). Diabetes (58.02%) and hypertension (53.09%) were the most common comorbidities. Hyperuricemia was present in 66.04% of patients, with a mean serum uric acid level of 8.24 ± 3.13 mg/dL. AKI was significantly associated with hyperuricemia (p<0.0001). Elevated lactate levels (>2.2 mmol/L) were found in 98.13% of hyperuricemia patients, indicating hemodynamic instability. Vasopressor support was more frequently required in the hyperuricemia group, with 38% needing two or more vasopressors versus 16.7% in the normouricemia group (p<0.001). Additionally, 35.51% of hyperuricemia patients required mechanical ventilation compared to 3.63% in the normouricemia group (p<0.001). In-hospital mortality was also significantly higher in the hyperuricemia group (p=0.0194), although 30-day mortality did not reach statistical significance (p=0.2248). Conclusion: Hyperuricemia in sepsis is significantly associated with worse clinical outcomes, including acute kidney injury, need for multiple vasopressors, assisted mechanical ventilation, and increased in-hospital mortality. Serum uric acid may serve as a useful biomarker for risk stratification in septic patients.